THE INFLUENCE OF SERVICE DIGITALIZATION AND TECHNOLOGY COMPETENCY ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE ADAPTABILITY AT BANK BRI SAMARINDA GAJAH MADA BRANCH - Ariani; Irsan Tricahyadinata; Wirasmi Wardhani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Digital transformation in the banking sector requires employees not only to operate technology-based service systems, but also to adjust their work behavior quickly, flexibly, and productively. This study aims to analyze the influence of service digitalization and technology competence on employee performance and to examine the mediating role of employee adaptability at Bank BRI Samarinda Gajah Mada Branch. This research employed a quantitative explanatory design. The research population consisted of all 149 employees at Bank BRI Samarinda Gajah Mada Branch; therefore, a census or saturated sampling technique was applied. Data were collected using a Likert-scale questionnaire and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that service digitalization has a positive and significant effect on employee adaptability and employee performance. Technology competence also has a positive and significant effect on employee adaptability and employee performance. Furthermore, employee adaptability positively and significantly affects employee performance and partially mediates the effect of service digitalization and technology competence on employee performance. These findings confirm that successful banking digital transformation depends not only on technological infrastructure, but also on employees' readiness to adapt to changing work processes. This study recommends strengthening technology training, change-management support, and an adaptive work culture to ensure that service digitalization translates into sustainable performance improvement.